THEORY AND METHODS OF TEACHING ENGLISH TO YOUNG LEARNERS - Abdugopporova Odinaxon Hoshimjon qizi (Лучшие интеллектуальные исследования, 2024)
Abstract: This article aims to help young school teachers understand the characteristics of the different methods used in teaching a foreign language to avoid difficulties in teaching a foreign language and to achieve good results taking into account the individual needs of young learners.